New Economics Journals - Economics Bibliography, Journal of (Journal of Economics Bibliography, 2016)
This list is consisted of the journals that entered to EconBib Index created by KSP. The list is updated with the each volume of JEB and incorporated the new added journals to EconBib. Please visit the official EconBib website www.econbib.org to see the contents of each journal. The journals, which may want to enter to the list and be indexed by EconBib, may find the conditions in EconBib website. “The register form” in the website should be submitted to the stated e-mail address. All journals within EconBib are updated automotically when new volumes of JEB are published. Detailed information about EconBib can be found in its website www.econbib.org.